Understanding the Use and Application of Meme Marketing in Strategic Communications in Bangladesh - Ahona, Tasnuva Alam (Journal of Journalism and Media, 2024)
As a strategic communication tool, meme marketing is successfully connected with modern audiences, automatically assuming its preference in the Bangladeshi strategic communication field. However, there has yet to be any comprehensive study about whether this strategy is as effective as it is in other areas of the world as opposed to Bangladesh. Duplicating a strategy that worked well in other areas does not confirm success here, and there needs to be concrete proof of how to make this work here, considering the country's specific contexts and the associated culture. This study drew insights from heavy meme consumers of Bangladesh through a comprehensive analysis of survey responses. The participants were picked from the leading meme groups on Facebook and through a purposive sampling. The survey found out about the participants' meme source preferences and the correlation between their liking a meme and their buying behavior. It also included if they did not like a meme, then what were the reasons behind it. Furthermore, participants' criticisms and suggestions were also included in the paper on how to make the strategy a better-implemented tool. As a guide for the users of this tool as a means of strategic communication, the matters of ethical considerations and cultural appropriateness were thoroughly discussed. This study concludes with a holistic understanding of memes as a strategic communication tool in digital culture.